Study of the effective temperatures of two neutron moderating materials: Ethane and triphenylmethane - Robledo, José Ignacio; Dawidowski, Javier; Cantargi, Florencia Olga; Granada, Jose Rolando; Rodriguez Palomino, Luis Alberto; Romanelli, G.; Krzystyniak, M.; Cuello, Gabriel Julio; Helman, C. S.; Skoro, G. (Elsevier Science, 2023)
Fil: Robledo, José Ignacio. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina